The Effects of Promotional Efforts Based on Gender Characteristics on Knowledge and Practice of Personal Genital Hygiene among Students of SD Negeri Ledug - Sulistia, Mahfuroh; Deisy Sri Hardini (Universitas Airlangga, 2025)
Background: Hygiene behavior is very important to prevent children and adolescents from falling into various forms of sexual violence which are increasingly common in this millennial era. It is important to provide sexual education from an early age. Objectives: This research aims to identify the influence of promotive efforts based on gender characteristics on the knowledge and practice of personal genital hygiene in Ledug State Elementary School students. Methods: This was quantitative research with a quasi-experimental design with a Solomon four-group approach. The sample was 70 respondents using the simple random sampling method. Data analysis used the one-way ANOVA test. Results: The results of this research are the results of the one-way ANOVA statistical test which obtained a p-value of 0.000 which means p < 0.05; for knowledge, the average result of the female intervention group was greater, with a score of 29.3. Meanwhile, the skill that had the highest average value was the male intervention group, with a score of 19.4. Conclusion: There is an effect of promotional efforts based on gender characteristics on knowledge and practice of personal genital hygiene among students of SD Negeri Ledug. Ledug Elementary School students are expected to have a greater desire to know and a better way of thinking to gain knowledge, intellectual skills, and problem-solving skills.